A141 ENDOSCOPIST PROCEDURAL VOLUME AND COLONOSCOPY OUTCOMES: A SYSTEMATIC REVIEW AND META-ANALYSIS. (26th February 2020) - Forbes, N; Boyne, D; Brenner, D R; Mazurek, M S; Hilsden, R J; Ruan, Y; Sutherland, R L; Pader, J; Shaheen, A M; Lamidi, M; Heitman, S
Abstract: Background: In addition to monitoring adverse events (AEs) and post-colonoscopy colorectal cancers (PCCRC), several indicators are used to assess the overall quality of colonoscopy performance, including adenoma detection rate (ADR) and cecal intubation rate (CIR). It is unclear whether there is an association between an endoscopist's annual colonoscopy volumes and ADR, CIR, AEs or PCCRC. Aims: We performed a systematic review and meta-analysis to determine whether there is an association between annual colonoscopy volume and colonoscopy quality indicators, or between annual volume and colonoscopy outcomes. Methods: A comprehensive electronic search was performed through March of 2019 for any studies assessing the potential association between annual colonoscopy volume and outcomes, or quality indicators, including ADR, CIR, AEs or PCCRC. Pooled odds ratios (OR) were calculated using DerSimonian and Laird random effects models. Subgroup and sensitivity analyses were also performed to assess for any potential methodological or clinical factors associated with outcomes. These included dividing procedural volume into total procedures or screening procedures performed. Results: Out of an initial 9, 235 studies, 27 were included in our systematic review, representing 11, 276, 244 colonoscopies performed by over 530 endoscopists. There was no association between procedural volume and ADR (OR 1.00, 95% confidence intervals, CI, 0.98 to 1.02 per additional 100 annual total colonoscopy procedures performed by an endoscopist). CIR was improved with each additional 100 annual colonoscopy procedures (OR 1.17, 95% CI 1.08 to 1.28). There was a trend toward decreased overall adverse events per additional 100 annual procedures that did not meet significance (OR 0.95, 95% CI 0.90 to 1.00), although there was a decreased incidence of colonic perforations with increasing colonoscopy volume. Figure 1 - Forest plots demonstrating the odds of A) detecting an adenoma, B) intubating the cecum, and C) incurring an overall or specific adverse event, per additional 100 annual procedures, for total and screening procedures. Conclusions: In this meta-analysis, higher annual colonoscopy volumes correlated with higher CIR, but not with ADR or PCCRC. Trends toward lower AE rates were also demonstrated with higher volumes. All studies included in this review examined endoscopists performing above respective recommended minimum volume thresholds for their health region. Thus, data are lacking on endoscopists performing very low numbers or very high numbers of colonoscopies annually. Future studies should focus on measuring colonoscopy quality metrics and outcomes among these extreme performers to more clearly determine associations between annual volume and colonoscopy outcomes. Funding Agencies: Alberta Health Services Digestive Health Strategic Care Network